Merevolusi Batik: Bagaimana Fintech Memberdayakan UMKM Malang untuk Pertumbuhan Ekonomi - nandiroh, Umi; Irma Hidayati; Puji Handayati; Agus Hermawan (CV. AFDIFAL MAJU BERKAH, 2024)
The study looks at how MSME's traditional business practices are being revolutionized by fintech, digital financial services, especially given Indonesia's burgeoning digital economy. The difficulty of MSMEs in obtaining Standard Financial Services is a major issue in this study, which has historically hindered their ability to grow and run more efficiently. Fintech solutions are becoming an important tool for small businesses because of their accessibility, cost efficiency, and simple procedures. Batik Malang MSMEs can break through financial barriers, gain access to new markets, and become more competitive by implementing fintech. Using in-depth interview techniques with owner Samtana Indonesia, one of Malang Batik entrepreneurs. The research explores a range of fintech services, including online lending platforms, digital payments, and e-commerce integration, showing how these services can promote a wider range of consumers, better financial management, and higher sales. Fintech integration improves the overall performance and sustainability of these MSMEs by enabling them to interact with the digital economy, which is not limited to a single country. The results of this case study also address the broader impact of fintech adoption on the Indonesian economy. It highlights how fintech is helping to advance financial inclusion, especially for small and medium-sized businesses, which is critical to Indonesia's economic expansion. In conclusion, the results of this study offer a thorough insight into how fintech adoption is transforming Batik Malang MSMEs, emphasizing the role of fintech adoption in increasing business productivity, expanding financial accessibility, and advancing Indonesia's overall economic growth.